Telework: A Systematic Literature Review (SLR) - Bahariawansyah, Ahmad Sidqi; Nadia, Fiona Niska Dinda (Ekonika : Jurnal Ekonomi Universitas Kadiri, 2024)
The application of the telework work system in this era has been applied to all lines of the Company's field. The purpose of this systematic review literature review is to analyze how the implementation of the Telework work system using the Preferred Reporting Items for Systematic Review method. Data was obtained from the online database, namely Scopus with a range of 2021 to 2023 and 53 articles were obtained. By using keyword searches, namely "telework" and "teleworking". The results of the analysis obtained show that the implementation of a telework work system has an implementation, namely the environment and conditions of telework work, work improvement, work arrangements, control of working time, relationships with colleagues, interruptions and intrusions when working telework, increasing flexibility, welfare, organizational competitiveness, job satisfaction, work performance, improving the relationship between managers and subordinates, to a well-developed work-life balance.